Proteins with H-bond packing defects are highly interactive with lipid bilayers: Implications for amyloidogenesis - Fernandez, Ariel (2003)
We noticed that disease-related amyloidogenic proteins and especially cellular prion proteins have the highest proportion of incompletely desolvated backbone H bonds among soluble proteins. Such bonds are vulnerable to water attack and thus represent structural weaknesses. We have measured the adsorption of proteins onto phospholipid bilayers and found a strong correlation between the extent of underwrapping of backbone H bonds in the native structure of a protein and its extent of deposition on the bilayer: the less the H bond wrapping, the higher the propensity for protein-bilayer binding. These observations support the proposition that soluble proteins with amyloidogenic propensity and membrane proteins share a pervasive building motif: the underwrapped H bonds. Whereas in membrane proteins, this motif does not signal a structural vulnerability, in soluble proteins, it is responsible for their reactivity.